EFISIENSIPEMANEAATAN NPV DAN Trichogramma UNTUK PENGENDALIAN ULAT BUAH KAPAS HeUcoverpa armigera HBN - SRI HADIYANI; IG. A.A. INDRAYANI; S. A. WAHYUNI; D. A. SUNARTO; SUPRAPTO SUPRAPTO; HARJYANTO HARJYANTO (Pusat Penelitian dan Pengembangan Perkebunan, 1999)
The purpose of this esearch was to study the efficiency in using HeUcoverpa armigera Nuclear Polyhedrosis Virus (HaNPV) and Trichogrammatoidea armigera Nagaraja to improve and simplify' Integrated Pest Control recommendation package for farmers. This research was conducted in Asembagus Experimental Station, Situbondo, East Java, from December 1997 to May 1998. Cotton plants were planted in monocultue system and the pests were controlled using IPM-3 recommendation package. This research was designed in randomized block with 3 treatments, and 3 eplicates. HaNPV spraying was based on the treshold; releasing T. armigera was based on the theshold, and the schedule of insecticide spraying was every 10 days. The esult showed that treatment of eleasing T armigera followed by application of insecticide was the most efficient (B/C ratio ■ 1.39), compared with the insecticide spraying schedule (B/C ratio = 1.21), and spraying of HaNPV fB/C ratio =1.12).